2022
DOI: 10.3389/fpls.2022.898220
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Morphological Characterization and Nutritional Profiling of Traditional Himalayan Crop Landraces for Their Promotion Toward Mainstream Agriculture

Abstract: The northwest Indian Himalayas are often regarded as a biological hotspot for the presence of rich agro-biodiversity harboring locally adapted traditional crop landraces facing utter neglect owing to modern agricultural systems promoting high-yielding varieties. Addressing this challenge requires extricating the potential of such cultivars in terms of agro-morphological and nutritional attributes. In this study, 29 traditional crop landraces of maize (11), paddy (07), finger millet (03), buckwheat (05), and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
1
2
Order By: Relevance
“…On the contrary, Malhotra et al. ( 2022 ) studied nutritional profiling of rice landraces from northwest Indian Himalayas and found significant differences in protein content among rice landraces of Himachal Pradesh and Uttarakhand, for example, they reported protein 14.86 g/100 g in Lamgudi dhan which is much higher than the results of the present study. These variances are primarily associated with an alteration in their geographical origin (Kumar et al., 2015 ).…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…On the contrary, Malhotra et al. ( 2022 ) studied nutritional profiling of rice landraces from northwest Indian Himalayas and found significant differences in protein content among rice landraces of Himachal Pradesh and Uttarakhand, for example, they reported protein 14.86 g/100 g in Lamgudi dhan which is much higher than the results of the present study. These variances are primarily associated with an alteration in their geographical origin (Kumar et al., 2015 ).…”
Section: Resultscontrasting
confidence: 94%
“…These results are comparable with other reports that the Korean rice landraces contain 6.99 g/100 g protein (Li et al, 2014) and 6.7 g/100 g protein reported in LELLI AAM, Arunachal rice landraces (Longvah & Prasad, 2020) indicating the potentiality of these varieties as a functional food. On the contrary, Malhotra et al (2022) studied nutritional profiling of rice landraces from northwest Indian Himalayas and found significant differences in protein content among rice landraces of Himachal Pradesh and Uttarakhand, for example, they reported protein 14.86 g/100 g in Lamgudi dhan which is much higher than the results of the present study. These variances are primarily associated with an alteration in their geographical origin (Kumar et al, 2015).…”
Section: Proximate Compositioncontrasting
confidence: 99%
“…Specifically, Pop18 had an average seed weight of 32 g per 1000 seeds. The most recent study on morphological traits among common buckwheat landraces, conducted on Himalayan germplasm, reported that the 1000 seed weight among their accession ranged between 17.42 and 22.64 g [46]. One of the less desirable traits found in Pop18 is its stem color, which was green.…”
Section: Phenotypic Data On Common Buckwheat Accessionsmentioning
confidence: 99%